Aortocaval compression resulting in sudden loss of consciousness and severe bradycardia and hypotension during cesarean section in a patient with subvalvular aortic stenosis - Shouming Chen; Lan Wu; Xiaoqin Jiang (BMC Anesthesiology, 2019)
Abstract Background Maternal cardiac arrest during cesarean section (CS) is an extremely rare but devastating complication. Preventing emergency events from developing into maternal cardiac arrest is one of the most challenging clinical scenarios. Case presentation A 35-year-old pregnant woman with subvalvular aortic stenosis who was scheduled for elective CS under epidural anesthesia, and experienced devastating supine hypotensive syndrome, but was successfully resuscitated after delivery. Conclusions The performance of tilt position strictly or high-quality continue manual left uterine displacement (LUD) should be performed until the fetus is delivered, otherwise timely delivery of the fetus may be the best way to optimize the deadly condition.